Sporadic non-functioning pancreatic neuroendocrine tumours: multicentre analysis. Issue 7 (16th March 2021) - Ricci, C; Partelli, S; Landoni, L; Rinzivillo, M; Ingaldi, C; Andreasi, V; Nessi, C; Muffatti, F; Fontana, M; Tamburrino, D; Deiro, G; Alberici, L; et al.
Abstract: Background: Outcomes after surgery for sporadic pancreatic neuroendocrine neoplasms (Pan-NENs) were evaluated. Methods: This multicentre study included patients who underwent radical pancreatic resection for sporadic non-functioning Pan-NENs. In survival analysis, the risk of mortality in this cohort was analysed in relation to that of the matched healthy Italian population. Relative survival (RS) was calculated as the rate between observed and expected survival. Factors related to RS were investigated using multivariable modelling. Results: Among 964 patients who had pancreatic resection for sporadic non-functioning Pan-NENs, the overall RS rate was 91.8 (95 per cent c.i. 81.5 to 96.5) per cent. 2019 WHO grade (hazard ratio (HR) 5.75 (s.e. 4.63); P = 0.030) and European Neuroendocrine Tumour Society (ENETS) TNM stage (6.73 (3.61); P < 0.001) were independent predictors of RS. The probability of a normal lifespan for patients with G1, G2, G3 Pan-NENS, and pancreatic neuroendocrine carcinomas (Pan-NECs) was 96.7, 54.8, 0, and 0 per cent respectively. The probability of a normal lifespan was 99.8, 99.3, 79.8, and 46.8 per cent for those with stage I, II, III, and IV disease respectively. The overall disease-free RS rate was 73.6 (65.2 to 79.5) per cent. 2019 WHO grade (HR 2.10 (0.19); P < 0.001) and ENETS TNM stage (HR 2.50 (0.24); P < 0.001) significantly influenced disease-free RS. The probability of disease-free survival was 93.2, 84.9, 45.2, and 6.8 per cent for patients with stage I, II, III, and IV disease, and 91.9, 45.2, 9.4, and 0.7 per cent for those with G1, G2, G3 Pan-NENS, and Pan-NECs, respectively. Conclusion: A surgical approach seems without benefit for Pan-NECs, and unnecessary for small G1 sporadic Pan-NENs. Surgery alone may be insufficient for stage III–IV and G3 Pan-NENs. Abstract : Surgical therapy for sporadic pancreatic neuroendocrine neoplasms might be considered excessive, insufficient, or appropriate. In this study, survival analysis was carried out using the cure model approach. The analysis suggested: an excellent prognosis for sporadic G1 pancreatic neuroendocrine tumours (Pan-NETs); the value of surgical management of all G2 Pan-NETs, underlying an unmet need for a multimodal approach for stage III–IV disease; the need for a multimodal strategy for all G3 Pan-NETs; and the probable futility of upfront radical surgery for most neuroendocrine carcinomas. choose well